Variations in Litterfall Dynamics, C:N:P Stoichiometry and Associated Nutrient Return in Pure and Mixed Stands of Camphor Tree and Masson Pine Forests - Farooq, Taimoor Hassan; Li, Zhongwen; Yan, Wende; Shakoor, Awais; Kumar, Uttam; Shabbir, Rubab; Peng, Yuanying; Gayathiri, Ekambaram; Alotaibi, Saqer S.; Wróbel, Jacek; kalaji, Hazem M.; Chen, Xiaoyong (Frontiers in Environmental Science, 2022)
Litterfall, directly and indirectly, affects the soil physicochemical properties, microbial activity, and diversity of soil fauna and flora by adding organic matter and nutrients to the soil. This study explores litterfall dynamics such as litterfall production, litter decomposition rate, and associated nutrient return in three forest types, that is, camphor tree forest (CTF), Masson pine forest (MPF), and camphor tree and Masson pine mixed forest (CMF), in subtropical China. Results showed that CMF had the highest mean annual litterfall production (4.30 ± 0.22 t ha−1), which was significantly higher than that of MPF (3.41 ± 0.25 t ha−1) and CTF (3.26 ± 0.17 t ha−1). Leaf represented the major fraction of litterfall, constituting over 71% of the total litterfall mass in the three forest types. The contribution of branch litter was 16.3, 8.9, and 16.9%, and miscellaneous litter was 12.6, 18.9, and 11.1% in CTF, MPF, and CMF, respectively. The concentration of macronutrients ranked as N > Ca > K > Mg > P in all litter fractions. The total annual macronutrient return to the soil from the litterfall was in order as CTF (74.2 kg ha−1‧yr−1) > CMF (70.7 kg ha−1‧yr−1) > MPF (33.6 kg ha−1‧yr−1). The decomposition rate was higher in leaf litter than in branch litter throughout the three forests. Among the forest types, the leaf and branch decomposition rates were in a pattern: CTF > CMF > MPF. The ratio of C/N in both leaf and branch litters was significantly higher in MPF than in CTF and CMF, while no significant differences in N/P ratio were found in these litters among the three forests. The high N:P ratios in leaf litter (23/30) and the branch (24/32) litter indicated the high N returning and low nutrient returning to the soil. Our results suggested that the broadleaved forests have faster litter decomposition and higher macronutrient returns than conifer forests. Moreover, the litter decomposition rate was mainly associated with litterfall quality and chemical composition. The introduction of broadleaved trees into monoculture coniferous stands could increase litter production nutrients return, and thus, it had advantages in soil nutrients restoration and sustainable forest management.